The Effect of Regional Fiscal Capacity on Climates Change Action Budgeting Commitments - Golfred Alex Kojongkam; Sukirman Rahim; Iswan Dunggio (Universitas Gorontalo, 2022)
This journal aims to determine the effect of regional fiscal capacity on climate change action budgeting commitments. The research method used is a quantitative method with a statistical test approach to Structural Equation Modeling (SEM). The results of this study indicate that the local government's fiscal capacity of Gorontalo Regency has a significant positive direct influence on climate change action budgeting commitments.